2018
DOI: 10.1159/000492303
|View full text |Cite
|
Sign up to set email alerts
|

A Trypsin-Sensitive Proteoglycan from the Tapeworm <b><i>Hymenolepis diminuta</i></b> Inhibits Murine Neutrophil Chemotaxis in vitro by Suppressing p38 MAP Kinase Activation

Abstract: It has emerged that neutrophils can play important roles in the host response following infection with helminth parasites. Mice infected with the tapeworm, Hymenolepis diminuta, are protected from some inflammatory conditions, accompanied by reduced neutrophil tissue infiltration. Thus, the ability of a phosphate-buffered saline-soluble extract of the worm (H. diminuta extract [HdE]) was tested for (1) its ability to activate murine neutrophils (Ca2+ mobilization, reactive oxygen species (ROS) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These immunoregulatory strategies protect gastrointestinal tapeworms (such as D. caninum ) from being ejected by the immune response but also provide protection to the host (only when present in moderate numbers) against gastrointestinal inflammatory diseases that result from a dysfunctional immune system. For example, the high molecular weight extracts of the rat tapeworm, Hymenolepis diminuta , has been shown to protect mice against experimental colitis and arthritis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These immunoregulatory strategies protect gastrointestinal tapeworms (such as D. caninum ) from being ejected by the immune response but also provide protection to the host (only when present in moderate numbers) against gastrointestinal inflammatory diseases that result from a dysfunctional immune system. For example, the high molecular weight extracts of the rat tapeworm, Hymenolepis diminuta , has been shown to protect mice against experimental colitis and arthritis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…brasiliensis [ 49 ] and in vitro analysis has shown that an extract of H . diminuta directly affects migration of both of these cell types [ 50 , 51 ]. Complementing previous publications that show increased Foxp3 mRNA expression in infected mice [ 29 , 52 ], Foxp3 + T cells were increased in the Peyer’s patches of infected Pou2f3 +/+ .…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Furthermore, tryptase-activated neutrophils have traditionally been viewed as a frontline defence against microbial infections, carrying proteases that can destroy invaders but might also cause considerable collateral damage to the host. 32 Once activated, neutrophils release soluble factors and granules into the extracellular environment both to facilitate their translocation, and to promote fixation or killing of pathogens. 33 Neutrophil degranulation has been associated with the pathogenesis of dry eye, as has upregulated release of various soluble inflammatory mediators including MMP-9, lysozyme and tryptase.…”
Section: Source and Action Mechanism Of Tryptasementioning
confidence: 99%